Analisis Perubahan Makna Meluas (Generalisasi) Dan Perubahan Makna Total Dalam Media Sosial Instagram - Salma Janiya Salsabilla (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This study is motivated by language where language always produces new words and new meanings that aim to fulfill the need for communication. The problem discussed is how many changes in meaning are widespread and changes in total meaning are found in statuses, captions, and comments on Instagram social media, and how changes in meaning are widespread when compared to the denotative meaning or actual meaning. The purpose of this study is to find out how widespread changes in meaning and changes in total meaning are found in statuses, captions, and comments on Instagram social media, and to find out how changes in meaning extend and change in total meaning when compared to denotative meanings or actual meanings. Research methods used in this study using qualitative methods. Based on the results of the discussion, 9 (nine) forms of changes in broad meaning were found, and 5 (five) changes in total meaning